Bilateral Chylothorax as a Unique Presentation of Pancreaticobiliary or Upper Gastrointestinal Cancer - Nooraldin Merza; John Lung; Mazin Saadaldin; Tarek Naguib (Case Reports in Pulmonology)
Chylothorax presents as exudate with lymphocytic predominance and high triglyceride-low LDH levels, usually due to a traumatic disruption of the thoracic duct, possibly iatrogenic. Other causes include malignancy, sarcoidosis, goiter, AIDS, or tuberculosis. Here we present a case of a 66-year-old male who came in with cough and shortness of breath for few weeks. A week earlier, at an ED visit, he was diagnosed with pneumonia based on CT angiogram of the chest without contrast that showed bilateral pleural effusion and bilateral pulmonary infiltrates. The CT-guided placement of bilateral chest tube drained 1160 cc of creamy yellow fluid on the right and 1200 cc of creamy yellow fluid on the left. CT chest/abdomen/pelvis showed bilateral ground-glass opacities within the lungs and possible bony metastasis. A whole-body bone scan showed multiple bony metastatic lesions throughout the skeleton. IR guided bone biopsy suggested upper GI or pancreaticobiliary cancer. Venous ultrasound with Doppler of left upper extremity showed findings suggestive of a nonocclusive DVT of proximal/mid left subclavian vein which is difficult to compress. Eventually, malignancy-related DVT of the left subclavian/brachiocephalic vein was identified as the possible etiology for the bilateral chylothorax.